ETNOGRAFI RUANG KELAS: NEGOSIASI BUDAYA KURIKULUM CINTA DALAM MEMBANGUN KESETARAAN DI KELAS BAHASA INGGRIS YANG HETEROGEN - Halimatus Sya’diyah; Sinta Bella; Siti Asiya (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study examines how the “Curriculum of Love” is culturally negotiated within heterogeneous English language classrooms to foster educational equity. The central issue addressed is the persistence of power asymmetries, sociocultural disparities, and instrumental pedagogical practices that marginalize affective and ethical dimensions of language education. This research aims to analyze the forms, processes, and meanings of the Curriculum of Love as enacted in classroom interactions and its contribution to equitable learning. Employing a qualitative approach with classroom ethnography, data were collected through participant observation, in - depth interviews, and instructional document analysis. The findings reveal that the Curriculum of Love operates as a reflective pedagogical practice that mediates differences, reduces symbolic hierarchies, and strengthens empathetic relationships between teachers and students. Cultural negotiation emerges through language use, inclusive teaching strategies, and recognition of students’ identities. The study concludes that the Curriculum of Love extends beyond normative discourse, functioning as a transformative cultural practice in language education. The novelty of this research lies in conceptualizing the Curriculum of Love as a mechanism of cultural negotiation that advances equity and social justice within heterogeneous English classrooms.